Review on The Inclusion Of The Exoneration Clause In The Standard Clause Based On Law No 8 Of 1999 Concerning Consumer Protection - Sandi Nugraha; Gunawan Nachrawi (LEGAL BRIEF, 2022)
This study aims to obtain information and analyze the law regarding consumer protection against standard agreements that include an exoneration clause and the responsibilities of business actors that include an exoneration clause. A standard agreement is an agreement where all the clauses are standardized by one party in the agreement without the participation of the other party which basically can eliminate the opportunity to request a change of the agreement. , or hidden defects. The standard agreement that includes the exoneration clause is prohibited because it is very contrary to the principles of good faith, the principle of balance, the principle of justice and especially the principle of freedom of contract which has been accommodated in Article 1338 of the Civil Code, Law Number 8 of 1999 concerning Consumer Protection in Articles 19 to Article 28 regulates the responsibilities of business actors in being accountable for all business activities carried out. Protection and supervision of consumers and business actors can be achieved by the existence of concern, involvement, and cooperation between the government, community, business actors, and (LPKSM) the existence of BPSK is expected to be achieved a sense of justice for all parties in conflict in consumer disputes, the government and law enforcement in this case (Polri Investigators, Civil Servants, Prosecutors, Judiciary and Advocates), must play an active role in monitoring and implementing the existence of this Consumer Protection Act, especially Article 18 aya t 1 About inclusion clause containing exoneration clause.